Structure–Function and Therapeutic Potential of Spider Venom-Derived Cysteine Knot Peptides Targeting Sodium Channels - Cardoso, Fernanda C.; Lewis, Richard J. (Frontiers in Pharmacology, 2019)
Spider venom-derived cysteine knot peptides are a mega-diverse class of molecules that exhibit unique pharmacological properties to modulate key membrane protein targets. Voltage-gated sodium channels are often targeted by these peptides to allosterically promote opening or closing of the channel by binding to structural domains outside the channel pore. These effects can result in modified pain responses, muscle paralysis, cardiac arrest, priapism and numbness. Although such effects are often deleterious, subtype selective spider venom peptides are showing potential to treat a range of neurological disorders, including chronic pain and epilepsy. This review examines the structure-activity relationships of cysteine knot peptides from spider venoms that modulate voltage-gated sodium channels and discusses their potential as leads to novel therapies for neurological disorders.